Penatagunaan Kawasan Sekitar Waduk dalam Upaya Menjaga Kelestariannya (Model DAM) - Nugroho, Hari; Suripin, Suripin (Department of Civil Engineering, Diponegoro University, 2013)
Kedungombo reservoir has provided a substantial contribution in improving the welfare of society, so that its existence should be preserved. As time goes there are some issues Kedungombo. The problems are concerning with the condition of reservoirs, dams and problems in the surrounding area. To preserve the reservoirs, conservation efforts by reviewing the management of the reservoir area. The study results showed that there was no master plan to utilize the management of Kedungombo catchment. For this reason, it is proposed the development of Kedungombo area is directed to recover the potential and cultivitation areas, to empower community and to strengthen the protected and cultivitation areas in order to concerved Reservoir. Kedungombo area is directed as a center of tourism services, housing, aquaculture and local protected areas. Reservoir area is specified to 500 meters from the boundary of the highest reservoir water level, so hopefully all the activities in this area follows specified to the regulations. It is recommended to develop an institution to manage Kedungombo Area. The institution should be able to implementation the principle of management i.e. transparency, open to various parties; can be accounted for; clarity the limits of authority, territory under the following management roles and responsibilities and apply the principles and legal norms in the management of the Area Kedungombo. The model is expected to be implemented and become a model for Reservoir Management in Indonesia.